Revenue mobilisation and utilisation among district assemblies in Ghana. - ODOOM GEORGE (KNUST, 2024)
A thesis submitted to the department of accounting and finance college of humanities and social sciences in partial fulfilment of the requirements for the degree of master of business administration (accounting).